EFEKTIFITAS EKSTRAK KUNYIT DALAM MENGURANGI NYERI DISMENORHEA PADA MAHASISWI DI ASRAMA AKADEMI KEBIDANAN SALMA SIAK - Indah Setia Ningsih, Siska Indrayani, (Menara Ilmu, 2018)
Incidence of dysmenorrhea in the Indonesia in 2014 amounted to 64.2%. Dysmenorrhea wasa common complaint women experience during menstruation. Dysmenorrhea often felt inthe lower abdomen, sometimes accompanied by dizziness, weakness, nausea and vomit thisusually occurs during menstruation or before menstruation. The cause of dysmenorrheapain was uterine muscle spasm that occur continuously at the time of menstruation.Dysmenorrhoe often experienced by female students and female students can not performtheir activities due to dysmenorrhea. One of the herbal method to reduced dysmenorrheapain by giving the extract of turmeric at the time of menstruation. The purpose of this studywas to determine the effectiveness of turmeric extract to reducing dysmenorhea pain infemale students at Dormitory Midwifery Academy of Salma Siak. The population in thisstudy were female students who experienced dysmenorrhea pain at the time of menstruation.The type of research used quantitative with quasy experimental with prestest and posttestcontrol group design. The technic of sampling in this study was purposive sampling that theselection of samples based on the characteristics or specific things with the population of 40female students. The research conducted at the Dormitory Midwifery Academy of SalmaSiak. The analysis used univariate and bivariate using T Independent test, with Pvalue<0,005 that is 0.000, it can be concluded that there is effectivity of giving of turmeric extractto reducing dysmenorrhea pain in female students at Dormitory Midwifery Academy ofSalma Siak. The Suggestion of research can help female students to reduce pain ofdysmenorrhea so that can follow learning from begin to end of study besides that studentsalso can make turmeric extract self at the time of dysmenorhea pain.Keywords: Turmeric Extract + Dysmenorrhea Pain